2012
DOI: 10.1353/hum.2012.0025
|View full text |Cite
|
Sign up to set email alerts
|

The Forced Labor Issue between Human and Social Rights, 1947-1957

Abstract: This article considers the question of forced labor in the framework of human and social rights, as unfolding in the early Cold War period. A precise analysis of the discussion surrounding the convention on the abolition of forced labor within the International Labour Organization (ILO) between 1947 and 1957 forms a basis for my observations. The conflict between the two blocs, like the decolonization process, demarcated a favorable period for defining the juncture between human and social rights. The alliance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The production of public knowledge – books, pamphlets, and conference reports – was central to the process by which amorphous categories such as ‘social progress’ and ‘social economy’ came to operate as a common-sense repertoire for transnational reform networks during this period (Rodgers, 2009). And this common language provided the basis for a distinctive internationalized social politics aiming to address apparently comparable problems across diverse regulatory contexts, a project in which the ILO featured prominently (Kott, 2012; Van Daele, 2005).…”
Section: Conceptual Framework: How Juridical Categorization Assembles...mentioning
confidence: 99%
“…The production of public knowledge – books, pamphlets, and conference reports – was central to the process by which amorphous categories such as ‘social progress’ and ‘social economy’ came to operate as a common-sense repertoire for transnational reform networks during this period (Rodgers, 2009). And this common language provided the basis for a distinctive internationalized social politics aiming to address apparently comparable problems across diverse regulatory contexts, a project in which the ILO featured prominently (Kott, 2012; Van Daele, 2005).…”
Section: Conceptual Framework: How Juridical Categorization Assembles...mentioning
confidence: 99%
“…These thoroughly anti-communist activities were reactivated at the beginning of the Cold War. In the absence of the ussr, the leading American union, the American Federation of Labour, used the ilo to campaign against forced labour in the ussr and the countries that would form the Eastern Bloc (Kott, 2012). After the ussr re-joined the Organization in 1954,2 the ilo became a platform for the two blocs to collaborate on the basis of a strong common belief in the need for more economic growth and increased productivity; this lasted until the crisis of 1977 and subsequent withdrawal of the United States from the ilo until 1980.…”
Section: Social Justice At the Heart Of The Ilo's Missionmentioning
confidence: 99%
“…For instance, the FrenchSwiss historian Sandrine Kott (2012) has shown that superpower rivalry at the International Labor Organization had a positive effect on the negotiations about, and the eventual creation of, international conventions on forced labor. In particular, Kott argues that coalitions between the Eastern Bloc countries and nations in the developing world forced concessions from the advanced capitalist countries.…”
Section: H Istoriog Rap Hical Gapsmentioning
confidence: 99%
“…Among a handful of Western scholars, however, the study of the communist past is shifting slightly, with more research being done on the cultural contributions of the Eastern Bloc, particularly with regard to the developing world. For instance, the French-Swiss historian Sandrine Kott (2012) has shown that superpower rivalry at the International Labor Organization had a positive effect on the negotiations about, and the eventual creation of, international conventions on forced labor. In particular, Kott argues that coalitions between the Eastern Bloc countries and nations in the developing world forced concessions from the advanced capitalist countries.…”
Section: Historiographical Gapsmentioning
confidence: 99%